The Effect of Terrorism on Consumer Confidence in Europe - Sharifullah, Maria Gulzar (2024)
A Master of Business Administration (MBA) thesis by Maria Gulzar Sharifullah entitled, “The Effect of Terrorism on Consumer Confidence in Europe”, submitted in December 2024. Thesis advisor is Dr. Khusrav Gaibulloev. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).